2016
DOI: 10.1042/bsr20160165
|View full text |Cite|
|
Sign up to set email alerts
|

Cucurbitacin E inhibits osteosarcoma cells proliferation and invasion through attenuation of PI3K/AKT/mTOR signalling pathway

Abstract: Cucurbitacin E (CuE), a potent member of triterpenoid family isolated from plants, has been confirmed as an antitumour agent by inhibiting proliferation, migration and metastasis in diverse cancer. However, the effects and mechanisms of CuE on osteosarcoma (OS) have not been well understood. The present study aimed to test whether CuE could inhibit growth and invasion of OS cells and reveal its underlying molecular mechanism. After various concentrations of CuE treatment, the anti-proliferative effect of CuE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Cucurbitacins have multiple therapeutic effects such as anti-inflammation, anti-proliferation, antiangiogenesis, and anti-cancer [452,[459][460][461][462]. Besides, cucurbitacins have also been elucidated as a potential candidate for various cancer therapies, including oral cell carcinoma, breast, ovarian, prostate, lung, gastric, bladder, and thyroid cancers, neuroastoma, hepatoma, and osteosarcoma [463][464][465][466][467][468][469][470][471][472][473][474][475]. Most of cucurbitacins have been reported with various anti-cancer activities, such as pro-apoptosis, anti-angiogenesis, autophagy induction, and inhibition of metastasis [452,[460][461][462]476].…”
Section: Cucurbitacinsmentioning
confidence: 99%
“…Cucurbitacins have multiple therapeutic effects such as anti-inflammation, anti-proliferation, antiangiogenesis, and anti-cancer [452,[459][460][461][462]. Besides, cucurbitacins have also been elucidated as a potential candidate for various cancer therapies, including oral cell carcinoma, breast, ovarian, prostate, lung, gastric, bladder, and thyroid cancers, neuroastoma, hepatoma, and osteosarcoma [463][464][465][466][467][468][469][470][471][472][473][474][475]. Most of cucurbitacins have been reported with various anti-cancer activities, such as pro-apoptosis, anti-angiogenesis, autophagy induction, and inhibition of metastasis [452,[460][461][462]476].…”
Section: Cucurbitacinsmentioning
confidence: 99%
“…Cucurbitacins are a family of natural products isolated from Cucurbitaceae plants, and possess a wide spectrum of pharmacological effects including anti-cancer, anti-diabetic, cytoprotective, and anti-inflammatory activities [15][16][17][18]. Cucurbitacin E (CuE), a highly oxygenated triterpene of cucurbitacins, is known to have a variety of pharmacological effects such as hepatoprotective, anti-inflammatory and anti-cancer activities [19][20][21][22][23][24]. Previous investigations have shown that CuE inhibits cell proliferation, migration, and invasion through different molecular mechanisms in vitro and in vivo, indicating that CuE exerts prominent investigation prospect in the treatment of various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Many diseases, including cancer, autoimmune diseases and neuropathy, are caused by disorders of the PI3K-Akt-mTOR signaling pathway (10). The PI3K-Akt-mTOR signaling pathway is related to several important mechanisms of cell growth, so a better understanding of the PI3K-Akt-mTOR signaling pathway contributes to the development of cancer drugs, and mTOR inhibitors have been previously developed and applied as novel antitumor targeting drugs (11).…”
Section: Introductionmentioning
confidence: 99%